Vulvovaginitis and the treatment of asymptomatic partners: a systematic review and meta-analysis - Giraldo, Paulo César; Rodrigues, Hugo Marcus; Melo, Amanda Gosson de; Amaral, Rose Luce do; Eleutério Junior, José; Gonçalves, Ana Katherine (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Treating sexual partners of women with vaginal candidiasis and bacterial vaginosis is a discussed topic. Despite the recommendations of international guidelines, doctors are still known to treat asymptomatic partners. Objective: To evaluate the influence of asymptomatic partner treatment in the cure and recurrence of vulvovaginitis in women. Methods: The following databases were searched using Mesh terms: PubMed, Embase, SciELO and CINAHAL. The selection criteria included randomized clinical trials published from 1982 to 2012. Studies involving pregnant women were excluded. Methodological quality was assessed using Jadad’s scale. Review Manager 5.1 was used for statistical analysis. Results: Eight randomized clinical trials were included based on the chosen criteria: 1,088 women were enrolled. For bacterial vaginosis, the relative risk for cure was 1.00 (95%CI 0.95–1.05, p=0.13), and for recurrence 0.84 (95%CI 0.62–1.14, p=0.34). Vaginal candidiasis had a RR of 1.03 (95%CI 0.94–1.14, p=0.48) for cure, and 1.02 (95%CI 0.77–1.33, p=0.91) for recurrence. Conclusion: Treatment of asymptomatic sexual partners of women with vaginal candidiasis or bacterial vaginosis does not affect the cure or recurrence rates and may increase the risk of side effects and unnecessary financial costs.